Rising Food and Energy Prices in Europe and Central Asia - World Bank (Washington, DC, 2017)
The purpose of this paper is to illustrate the channels through which rising commodity prices might affect countries in the Europe and Central Asia Region (ECA) in the short run and to indicate which countries are most likely to be significantly affected. This paper discusses the effects of the global food and energy price increases on ECA countries from two perspectives: (a) impacts on the macro-economy through inflation, the trade balance, fiscal accounts and growth; and (b) distributional impacts within countries. It aims to highlight vulnerabilities to rising commodity prices and discusses some policy interventions to mitigate the impact of rising prices. It puts the ECA experience in the context of the last commodity price increase as well the recent global economic crisis. Section one summarizes the state of global commodity markets. Section two discusses the main macroeconomic channels through which commodity price increases affect the economy. Section three discusses the potential poverty impacts of the price increases and the ability of countries' social assistance systems to deal with the heightened need for social assistance. It also discusses country responses to the crisis to date with reference to policies followed during the 2008 price hikes. Section four examines ECA's agriculture sector and potential responses to the commodity price increase and price volatility. Section five discusses the energy sector. Bank support to ECA countries to help deal with commodity market a development is discussed in annexes one.